2015
DOI: 10.1007/s11517-015-1269-8
|View full text |Cite
|
Sign up to set email alerts
|

Global sensitivity analysis of the joint kinematics during gait to the parameters of a lower limb multi-body model

Abstract: Sensitivity analysis is a typical part of biomechanical models evaluation. For lower limb multi-body models, sensitivity analyses have been mainly performed on musculoskeletal parameters, more rarely on the parameters of the joint models. This study deals with a global sensitivity analysis achieved on a lower limb multi-body model that introduces anatomical constraints at the ankle, tibiofemoral, and patellofemoral joints. The aim of the study was to take into account the uncertainty of parameters (e.g. 2.5 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 69 publications
1
31
2
Order By: Relevance
“…In MKO based on quaternions or rotation matrices, the initial guess at each sampled instant of time is often defined as the kinematics resulting from SKO applied to the skin markers [44,58]. MKO based on natural coordinates reported an initial guess of the points and axes describing the segments similarly obtained from the skin marker positions at each sampled instant of time [52,56,72]. As these natural coordinates enclose additional information about the segment geometry, the definition of the model geometrical parameters is also commonly derived from this initial guess by averaging segment lengths, position and orientations of joint centers and axis over all the sampled instants of time.…”
Section: Initial Guess and Model Geometric Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…In MKO based on quaternions or rotation matrices, the initial guess at each sampled instant of time is often defined as the kinematics resulting from SKO applied to the skin markers [44,58]. MKO based on natural coordinates reported an initial guess of the points and axes describing the segments similarly obtained from the skin marker positions at each sampled instant of time [52,56,72]. As these natural coordinates enclose additional information about the segment geometry, the definition of the model geometrical parameters is also commonly derived from this initial guess by averaging segment lengths, position and orientations of joint centers and axis over all the sampled instants of time.…”
Section: Initial Guess and Model Geometric Parametersmentioning
confidence: 99%
“…resulting standard deviation in model-derived joint kinematics reached up to 36° and 12 mm [72]. Sensitivity analyses demonstrated that STA had the most deleterious effect on hip gait kinematics [28,77], while errors in bony landmark location resulted in moderate effects [69,72,77,85]. Moreover, sensitivity of MKO to reduced marker sets [15,64] Journal of Biomechanical Engineering 20 showed good performance with less than three markers per body segment.…”
Section: Reconstruction Errormentioning
confidence: 99%
See 1 more Smart Citation
“…When the possible amount of an uncertainty is not available, the sensitivity of a particular output (e.g., joint kinematics, muscle moment arms, muscle function) to the change of an uncertain input (e.g., musculoskeletal geometry, musculotendon properties, joint axis location) can be quantified and provide valuable insights into the possible effects of lack of knowledge [5,16,17]. The impact of the uncertainty in different input parameters on several outputs of interest has been analyzed for musculotendon parameters [18][19][20][21][22], musculotendon geometry [23][24][25], joint center location [26], degree of freedom classification [27], joint models [28][29][30], skin marker placement [30], and pose estimation algorithms [31]. On the other hand, when the amount of possible uncertainty is known, an accurate evaluation of the output variability can be quantified.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have used probabilistic tools to analyze the effect of uncertain parameters on the output of interest [18][19][20][21][22][23][24][25][26][27][28][29][30][31], few of them have performed probabilistic analyses that combine multiple uncertainties belonging to different categories of parameters (described hereafter simply as "global") [36,37]. These global analyses allow a more complete investigation of the overall reliability of a model.…”
Section: Introductionmentioning
confidence: 99%